Testing of starch-based carbohydrate polymer coatings for enhanced urea performance - Naz, M.Y. (Springer Science and Business Media, LLC, 2014)
In this study, starch-urea-borate adhesives were developed for coating the slow release urea. The physical properties of the developed adhesives were studied as a function of temperature, heating time, stirring rate, and pH. It was found that for certain specific adhesive composition, pH and stirring rate, the complete gelatinization time and corresponding adhesive viscosity do not remain constant with temperature. The suspension heated at 75°C reached its maximum viscosity after 21 min of heating, thereafter, remained constant over time. In contrast, the suspension heated at 80°C reached its peak viscosity after 12 min of heating. Further heating after 12 min caused a steady decrease in viscosity from its peak value of 450-339 cP. Once the adhesive physical properties were completely understood, a dripping solution technique was used to coat the urea granules with coating thickness ranging from 0.15 to 0.7 mm. It was noticed that the overall nutrients release time of the coated urea was three times higher than the uncoated urea. It was also concluded that the mechanical strength of coated urea strongly depends on the adhesive composition and coating thickness. © 2014 American Coatings Association.